2021
DOI: 10.1007/s11356-021-15284-5
|View full text |Cite
|
Sign up to set email alerts
|

Baseline health risk assessment of trace metals in bivalve shellfish from commercial growing areas in the estuaries of Ashtamudi and Vembanad (Kerala, India)

Abstract: Trace metal concentrations were monitored in the yellow clam (Paphia malabarica), green mussel (Perna viridis) and edible oyster (Crassostrea madrasensis) from growing areas in the Ashtamudi and Vembanad estuaries, Kerala. Ranges of mean annual concentrations (mg/kg) were Ni (0.46-0.65); Co (2.87-3.49); Fe (80.0-119.4); Mn (3.88-9.38); Zn (40.8-76.2); Pb (1.28-2.00); . In Ashtamudi, clams had higher mean concentrations of Ni, Co, Fe, Mn and Pb than oysters. Mean concentrations of Ni, Pb (in all species), Zn (i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Fung et al [49] reported the concentrations (mg/kg dw) in P. viridis collected from Minjiang and Jiulongjiang (east coast of China) as Ni (2.97-4.78). Chinnadurai et al [50] reported that the Ni concentrations (0.46-0.79 mg/kg ww) in P. viridis were collected from the Vembanad Estuary, Kerala (India). As a result, the current Ni values are greater than those that were reported in the literature for the same mussel species.…”
Section: Comparison With Reported Studies and Food Safety Guidelines ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Fung et al [49] reported the concentrations (mg/kg dw) in P. viridis collected from Minjiang and Jiulongjiang (east coast of China) as Ni (2.97-4.78). Chinnadurai et al [50] reported that the Ni concentrations (0.46-0.79 mg/kg ww) in P. viridis were collected from the Vembanad Estuary, Kerala (India). As a result, the current Ni values are greater than those that were reported in the literature for the same mussel species.…”
Section: Comparison With Reported Studies and Food Safety Guidelines ...mentioning
confidence: 99%
“…Fung et al [49] (2004) reported the concentrations (mg/kg dw) in P. viridis collected from Minjiang and Jiulongjiang (east coast of China) as Cu (5.56-11.1). Chinnadurai et al [50] reported that the Cu concentrations (0.21-3.43 mg/kg ww) in P. viridis were collected from the Vembanad Estuary, Kerala (India). Aktar et al [55] reported the P. viridis collected from Cox's Bazar (Bangladesh) was 7.26 to 8.81 mg/kg dw for Cu.…”
Section: Cu Safety Guidelines and Comparison With Reported Studiesmentioning
confidence: 99%
See 1 more Smart Citation